STATE DUMA ELECTIONS IN THE PROVINCE OF THE DON COSSACK HOST AND POLITICAL PREFERENCES OF THE DON ELECTORATE - Maria Bratolyubova (Гуманитарные и юридические исследования)
The article studies regional peculiarities of the Don Cossack Host elections to the First and the Second State Duma of the Russian Empire. The author analyzes the conditions and features of election campaigns in the Don region, the political positions of the parties during the First and the Second State Duma elections, and shows how citizens got involved in the political life through elections. The peculiarities of forming political interests of the Don electorate and political fight for electorate as a factor of influence on the preferences of citizens are also addressed to in the article. It is argued that opposition sentiments of the society, typical of the greater part of the Don electorate, gave advantages to the "opposition parties" and their propaganda. The author concludes that agitation process showed superiority of Constitutional Democrats. On the one hand, the success of the party due to efficient organization of electoral company and reflection of the local needs of people in their political program. On the other hand, the discord of their political rivals, and the disability to organize and conduct the campaign at a high level proved to be important reasons for the fail. The success of Constitutional Democrats depended on their understanding of group interests of the Don electorate, Cossacks in particular. The article studies the composition of the regional electoral assembly. The author also gives the information about the deputies from the region with their class and political affiliations, and shows the connection between the development of the Don society politicization and the election process in the Duma of the first two convocation.